(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides a concise overview of effective strategies for teaching English to business students. It highlights the importance of integrating authentic business content into language instruction, fostering communicative competence, utilizing technology-enhanced learning tools, and addressing language proficiency assessment. By tailoring instruction to the unique linguistic and professional needs of business students, educators can empower them to succeed in the global marketplace.